Igaponera curiosa, a new ponerine genus (Hymenoptera: Formicidae) from the Amazon - Troya, Adrian; Marcineiro, Frederico; Lattke, John E.; Longino, John (European Journal of Taxonomy, 2022)
The monotypic ant genus Igaponera gen. nov. is proposed to include its type species I. curiosa (Mackay & Mackay, 2010). Igaponera gen. nov. is described and phylogenetically compared with other ponerine genera based on external morphology. The type species is known from a single gyne originally described in the genus Pachycondyla Smith, 1858. Igaponera curiosa is easily diagnosed by: costate sculpture on head, mesosoma, and petiole; short, robust, triangular mandibles with blunt apex; relatively large eyes set at mid-length on sides of head; lack of stridulitrum; and presence of distinct but relatively small arolia. Putative apomorphies of the new genus are: cuticular flange concealing metapleural gland opening; vertically standing hypostomal tooth with recessed base; stout mandibular shape with blunt apex; absence of stout spine-like setae on meso- and metatibial apices. Our phylogenetic results based on morphology suggest that Neoponera Emery, 1901 and Pachycondyla are the closest lineages to Igaponera, which shows intermediate characteristics as compared to those genera. The genus is apparently arboreal, known only from a seasonally flooded Igapó forest near Manaus, Brazil. Despite the collection site being frequented by researchers, no other specimens of this genus have been collected in over 40 years prior to this study.